2019
DOI: 10.1177/0265407519890414
|View full text |Cite
|
Sign up to set email alerts
|

Mean, uncommitted, and aggressive: Divergent associations between triarchic psychopathy, elements of love, and caustic relationship behaviors

Abstract: Two studies explored how the triarchic dimensions of psychopathy predicted relationship outcomes in nonclinical samples. In Study 1, using a predominantly student sample ( N = 100, 24% men, 76% women), results revealed significant negative associations between meanness and Sternberg’s (1997) components of love (intimacy, passion, and commitment). In Study 2, using a more gender-balanced online community sample ( N = 125, 53% men, 47% women), we replicated results from Study 1 and found additional negative asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 61 publications
2
6
0
Order By: Relevance
“…On the other hand, there were significant gender differences between relationships of psychopathy and commitment. Jonason et al (2013) and Mejia et al (2020) point that in general, Dark Triad traits are associated Dark Triad and Romantic Relationships Experiencing with avoidance of relationship commitment, but there are also studies where psychopathy (the secondary) was positively associated with all love components, commitment as well (Ali & Chamorro-Premuzic, 2010b). Our results showed that the more psychopatic women are, then less commitment in romantic relationship they experience and opposite, the more psychopatic men are, then stronger commitment they experience.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…On the other hand, there were significant gender differences between relationships of psychopathy and commitment. Jonason et al (2013) and Mejia et al (2020) point that in general, Dark Triad traits are associated Dark Triad and Romantic Relationships Experiencing with avoidance of relationship commitment, but there are also studies where psychopathy (the secondary) was positively associated with all love components, commitment as well (Ali & Chamorro-Premuzic, 2010b). Our results showed that the more psychopatic women are, then less commitment in romantic relationship they experience and opposite, the more psychopatic men are, then stronger commitment they experience.…”
Section: Discussionsupporting
confidence: 49%
“…Despite their personality, most subclinical psychopaths report that their relationship is not very intimate and, in some cases, involves partners outside the relationship (Ali & Chamorro-Premuzic, 2010a;Jones & Weiser, 2014), which points to low commitment. Psychopathic traits in subclinical samples such as meanness and psychological/physical aggression are also associated negatively with components of love, mainly intimacy and commitment (Mejia et al, 2020).…”
Section: Dark Triad and Romantic Relationships Experiencingmentioning
confidence: 99%
“… Love: Some studies have linked the typologies of love (specifically, Sternberg’s model) to IPA and psychopathy. Studies corroborated the existence of significant negative relationships between pettiness and the love components of Sternberg’s model (intimacy, passion, and commitment) [ 15 ]. These authors also found that deficits in love explained the increase in aggression towards the partner.…”
Section: Introductionmentioning
confidence: 79%
“…Before reviewing the literature more precisely, we note that some of the works focus on subjects diagnosed with psychopathy who were incarcerated after being convicted of attempted murder, others were convicted of homicide, others for both types of crimes [ 14 ], whereas other studies were performed with samples of students and the general population, usually focused on the dark personality [ 15 , 16 , 17 , 18 ]. This study will include two types of subsample, that of prisoners diagnosed with psychopathy who have murdered their intimate partner, and those also diagnosed with psychopathy and convicted of the attempted murder of their partner.…”
Section: Introductionmentioning
confidence: 99%
“…Reciprocally, efforts are being made to link the youth and adult literatures by evaluating whether replicable behavioral and brain correlates of callous-unemotionality, such as impaired recognition and deficient brain response to fear-face stimuli, extend to callousness in adults (Brislin et al, 2018; Brislin & Patrick, 2019). Research is also being conducted to test for affiliative deficits in relation to callous-unemotionality in adults (Mejia et al, 2020; Vieira & Marsh, 2014). Research of this kind, employing new and existing data sets—including etiologically informative (e.g., longitudinal, twin) data sets—to extend what we know about the nomological networks of these biobehavioral traits stands to greatly advance our understanding of the etiology and developmental course of psychopathy in the coming years.…”
Section: Christopher J Patrick: Conceptualizing and Understanding Psy...mentioning
confidence: 99%